Outcomes of head and neck surgery in patients with a history of solid organ transplantation. (4th July 2019) - Al‐Qurayshi, Zaid; Walsh, Jarrett; Owen, Scott; Randolph, Gregory; Kandil, Emad
Abstract : Objectives/Hypothesis: Examine the prevalence and outcomes of head and neck surgeries in patients with a history of organ transplantation. Study Design: A retrospective cross‐sectional analysis utilizing the Nationwide Readmissions Database, 2010 to 2014. Methods: The study population included adults patients who underwent head and neck surgeries. Patients with a reported history of solid organ transplantation were compared to patients with no such history. Results: The study population included 322 transplant patients (76.4% kidney, 8.7% liver, 8.4% heart, 3.0% kidney/pancreas, 2.3% lung, 0.9% kidney/liver, 0.4% pancreas) and 120, 401 controls who underwent comparable procedures. Main surgeries that were performed in cases included 37.8% parathyroid, 17.7% thyroid, 11.2% major salivary gland, 10.6% major mouth/tonsil, and 9.6% major nose/paranasal sinuses. Encountering transplant patients in otolaryngology practice has been increasing annually by three patients for every 10, 000 procedures performed in the United States. There was no difference in the overall postoperative complications risk (12.5% vs. 10.1%, P  = .26); however, cases had a higher risk of acute renal failure (5.4% vs. 1.1%, P < .001) and shock state (0.3% vs. 0.02%, P < .001). Readmission risk was higher for cases (6.8% vs. 3.4%, P  = .003). There was no reported in‐hospital mortality among cases. Conclusions: Transplant patients are increasingly encountered in otolaryngology practices. The most common transplanted organ is kidney, and the most commonly performed procedure is parathyroidectomy. Level of Evidence: NA Laryngoscope, 130:E89–E97, 2020